Differences in platelet‐rich plasma composition influence bone healing. (27th September 2021) - Al‐Hamed, Faez Saleh; Abu‐Nada, Lina; Rodan, Rania; Sarrigiannidis, Stylianos; Ramirez‐Garcialuna, Jose Luis; Moussa, Hanan; Elkashty, Osama; Gao, Qiman; Basiri, Tayebeh; Baca, Laura; Torres, Jesus; Rancan, Lisa; et al.
Abstract: Aim: Platelet‐rich plasma (PRP) is an autologous blood‐derived material that has been used to enhance bone regeneration. Clinical studies, however, reported inconsistent outcomes. This study aimed to assess the effect of changes in leucocyte and PRP (L‐PRP) composition on bone defect healing. Materials and Methods: L‐PRPs were prepared using different centrifugation methods and their regenerative potential was assessed in an in‐vivo rat model. Bilateral critical‐size tibial bone defects were created and filled with single‐spin L‐PRP, double‐spin L‐PRP, or filtered L‐PRP. Empty defects and defects treated with collagen scaffolds served as controls. Rats were euthanized after 2 weeks, and their tibias were collected and analysed using micro‐CT and histology. Results: Double‐spin L‐PRP contained higher concentrations of platelets than single‐spin L‐PRP and filtered L‐PRP. Filtration of single‐spin L‐PRP resulted in lower concentrations of minerals and metabolites. In vivo, double‐spin L‐PRP improved bone healing by significantly reducing the size of bone defects (1.08 ± 0.2 mm 3 ) compared to single‐spin L‐PRP (1.42 ± 0.27 mm 3 ) or filtered L‐PRP (1.38 ± 0.28 mm 3 ). There were fewer mast cells, lymphocytes, and macrophages in defects treated with double‐spin L‐PRP than in those treated with single‐spin or filtered L‐PRP. Conclusion: The preparation method of L‐PRP affects their composition and potential to regenerate bone.